Engineered heat treated methanogenic granules: a promising biotechnological approach for extreme thermophilic biohydrogen production - Abreu, A. A. (2010)
In the present study, two granular systems were compared in terms of hydrogen production rate, stability and bacterial diversity under extreme thermophilic conditions (70 °C). Two EGSB reactors were individually inoculated with heat treated methanogenic granules (HTG) and HTG amended with enrichment culture with high capacity of hydrogen production (engineered heat treated methanogenic granules – EHTG), respectively. The reactor inoculated with EHTG (REHTG) attained a maximum production rate of 2.7 l H2 l−1day−1 in steady state. In comparison, the RHTG containing the HTG granules was very unstable, with low hydrogen productions and only two peaks of hydrogen (0.8 and 1.5 l H2 l−1day−1). The presence of active hydrogen producers in the REHTG system during the reactor start-up resulted in the development of an efficient H2-producing bacterial community. The results showed that “engineered inocula” where known hydrogen producers are co-inoculated with HTG is an efficient way to start up biohydrogen-producing reactors.